EFEKTIVITAS FERMENTASI SUSU KAMBING DENGAN PENAMBAHAN Lactobacillus rhamnosus SEBAGAI INHIBITOR TIROSINASE (Fermentation Effectivity of Goat Milk added Lactobacillus rhamnosus as Tyrosinase Inhibitor) - Zuraida Hanum; Cece Sumantri; Purwantiningsih P; Irmanida Batubara; Epi Taufik (Universitas Syiah Kuala, 2016)
This study aimed to investigate the effectivity of goat milk fermentation as tyrosinase inhibitory with Lactobacillus rhamnosus TW 2. The examination of fresh milk contained the density, protein, and fat content. The culture of Lactobacillus rhamnosus TW 2 acid lactid bacteria starter was added with the concentration of 3, 4, and 5%, inoculated in pasteurized goat milk, then incubated at 37° C for 24 hours. Fermented milk were extracted by centrifugation, then supernatant was collected and was used for inhibition of tyrosinase enzymes activity on L-tyrosin and L-dopa substrate. The result showed that the density, fat content, and protein content of Etawah crossbred goat milk are 1.028, 3.73, and 5.45%, respectively. Re-identification of lactic acid bacteria showed similar morphology, physiology, and bio-chemistry with the isolated lactic acid bacteria. The growth curve of TW 2 was observed in 12 hours. The 5 % of Lactobacillus rhamnosus TW 2 was the best concentration to inhibit tyrosinase activity in L-Tyrosin substrate. In conclusion, fermentation of goat milk using Lactobacillus rhamnosus TW 2 at concentration of 5% as starter is effective to inhibit tyrosinase activity significantly.Key words: goat milk, fermentation, tyrosinase inhibitory